ASSESING THE ROLE OF MEDIA IN ECONOMIC DEVELOPMENT OF THE COMMUNITY: THE CASE OF THE SOUTH RADIO AND TELEVISION AGENCY, BONGA BRANCH IN DECHA WOREDA, SOUTHERN ETHIOPIA - BELACHEW BEKELE, WOGAYEHU (Innovare Journal of Social Sciences, 2021)
This study investigates the role of media in economic development of community in the case of South Radio and Television Agency Bonga branch Radio in Decha woreda, Kafa Zone in southern Ethiopia. The study has attempted to address the contribution of media in changing the audience’s knowledge, attitude, and practices in the community’s economic activities. In this study to address the objectives, a researcher applied mixed research approaches and descriptive design. Both primary and secondary data were used in the study and analyzed through qualitative and quantitative methods. To investigate information about the intended objective of the study, the data were collected through questionnaires, key informant interviews and focus group discussions. To determine the sample size for the study, multi-stage sampling technique was employed. Three Kebeles were selected purposively and 106 respondents participated in the study. The general finding of the study shows that Bonga branch radio has been influencing the behavior (attitude, knowledge and practice) of the community in their agricultural productivity, income generation, job creation and saving culture in its information transmits both in news and program formats in the community’s ethnic language. Even though, the media is playing its role in the community’s development, different challenges have been identified. Finally, the researcher tried to forward the recommendations; the local government should support the media, the media management should arrange training for the journalists and technician of the radio station and should take improving measures of transmission coverage of the radio station.